2020
DOI: 10.7759/cureus.11353
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin D Deficiency Among Infants in Northern India: A Hospital Based Prospective Study

Abstract: Background: Vitamin D deficiency is one of the major nutritional deficiencies and an important contributor to nutritional and growth failure in infants, especially in those with low socioeconomic status. Aim: The primary objective of this study was to determine the proportion of vitamin D deficiency in infants, and the secondary objective was to assess the correlation between infant and maternal vitamin D levels. Methods: This prospective, observational study was carried out at a tertiary care center, All Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
(48 reference statements)
0
6
0
4
Order By: Relevance
“…In India, 50-90% of the population suffers from vitamin D deficiency due to inadequate exposure to sunlight and a lower dietary intake [42][43][44]. A recent study from northern India reported the prevalence of vitamin D deficiency in 85.5% of mothers and 74% of infants [45]. Vitamin D deficiency, defined as <50 nmol/L of 25[OH]D and severe vitamin D deficiency defined as <30 nmol/L of 25[OH]D was reported in 34% and 18% of the population respectively in African countries [46].…”
Section: Developing Countriesmentioning
confidence: 99%
“…In India, 50-90% of the population suffers from vitamin D deficiency due to inadequate exposure to sunlight and a lower dietary intake [42][43][44]. A recent study from northern India reported the prevalence of vitamin D deficiency in 85.5% of mothers and 74% of infants [45]. Vitamin D deficiency, defined as <50 nmol/L of 25[OH]D and severe vitamin D deficiency defined as <30 nmol/L of 25[OH]D was reported in 34% and 18% of the population respectively in African countries [46].…”
Section: Developing Countriesmentioning
confidence: 99%
“…Читайте нас на сайті: http://med expert.com.ua профілактичного застосування [12,22,57], що призводить до труднощів точного визначен ня дефіциту вітаміну D. На рисунку і в таб лиці 1 наведено інтерпретацію рівнів 25 ОН D у сироватці крові за даними різних агенцій. Колірний код: червоний означає стан сильного дефіциту (недостатність), який слід виправити без винятку; помаранчевий -стан легкого дефіциту (помірне занепокоєння), при якому бажано втручання; зелений -стан достатнього постачання, при якому немає користі від додат кових добавок.…”
unclassified
“…За даними Американського ендокринного товариства [25] і більшості досліджень останніх років [12,22], дефіцитом вітаміну D в організмі вважають концентрацію 25 OH D <20 нг/мл (50 нмоль/л), а недостатністюконцентрацію 21-29,9 нг/мл (50-80 нмоль/л).…”
unclassified
See 2 more Smart Citations